Rebel talent why it pays to break the rules at work and in life - Gino, Francesca (Pan Books, 2019)
A behavioral scientist explores why "rebels" with unconventional outlooks who break the rules find the greatest success, discussing how they drive innovation and reinvention by defying the status quo
Includes bibliographical references (pages 231-269) and index
Keywords: Nonfiction / lcgft; Creative ability in business / fast / (OCoLC)fst00882438; Success in business / fast / (OCoLC)fst01137062; Success in business; Creative ability in business; Berufserfolg